Designing cities : basics, principles, projects - Schenk, Leonhard, 1965-; Fritz, Oliver; Futterer, Rolo; Neppl, Markus (Basel : Birkhauser, 2013)
Urban design is based on planning and design principles that need to meet functional demands on the one hand, but on the other hand bring the design elements together into a distinctive whole. Although designs are almost always dominated by the spirit of the times, the basic compositional principles are, for the most part, timeless.'Designing Cities' examines the most important design and presentation principles of urban design, using selected historical examples and contemporary international competition entries designed by practices including Foster + Partners, KCAP Architects & Planners, MVRDV, and OMA. At the core of the publication is the question of how the projects were designed and what methods and tools were available to the designer. In addition to the classic design that evolves in the mind of the designer, the repertoire is now expanding by means of new, computer-based methods, such as parametric design, in which variable parameters automatically influence the design and provide a range of possible solutions.
Includes bibliographical references (pages 346-349)
Keywords: City planning; Space (Architecture).